Phyto-Therapeutic and Nanomedicinal Approaches to Cure Alzheimer’s Disease: Present Status and Future Opportunities - Ovais, Muhammad; Zia, Nashmia; Ahmad, Irshad; Khalil, Ali Talha; Raza, Abida; Ayaz, Muhammad; Sadiq, Abdul; Ullah, Farhat; Shinwari, Zabta Khan (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is characterized by cognitive inability manifested due to the accumulation of β-amyloid, formation of hyper phosphorylated neurofibrillary tangles, and a malfunctioned cholinergic system. The degeneration integrity of the neuronal network can appear long after the onset of the disease. Nanotechnology-based interventions have opened an exciting area via theranostics of AD in terms of tailored nanomedicine, which are able to target and deliver drugs across the blood–brain barrier (BBB). The exciting interface existing between medicinal plants and nanotechnology is an emerging marvel in medicine, which has delivered promising results in the treatment of AD. In order to assess the potential applications of the medicinal plants, their derived components, and various nanomedicinal approaches, a review of literature was deemed as necessary. In the present review, numerous phytochemicals and various feats in nanomedicine for the treatment of AD have been discussed mechanistically for the first time. Furthermore, recent trends in nanotechnology such as green synthesis of metal nanoparticles with reference to the treatment of AD have been elaborated. Foreseeing the recent progress, we hope that the interface of medicinal plants and nanotechnology will lead to highly effective theranostic strategies for the treatment of AD in the near future.